Drones and their Role in the Evolution of Generations of War - Zaher, Assist. Prof. Dr. Rahman Abdel-Hussein (The International and Political Journal, 2023)
This research addresses a group of important issues related to drones that made a new revolution in modern warfare. These drones represent a new method of inflicting the largest losses on the enemy’s ranks, at low costs and without loss of pilots or aircraft. We discussed how the countries that possess these weapons, despite their small size, were able to find new balances that could soon portend the possibility of achieving larger and deeper balances with the major powers. What these aircraft achieved, for instance, in the wars of Yemen, Azerbaijan, Ethiopia, and others, can give a clear idea about this weapon, which represented a new military revolution capable of achieving strategic goals without losses